Estimating water density for tunnel fixed firefighting system and ventilation requirements to control fires in road tunnels. (March 2021) - Klein, Raymond; Maevski, Igor; Bott, Jeffrey; Calado, Andre
Abstract: A potentially dangerous fire event that can occur in road tunnels is a gasoline tanker fire, where flammable liquid fuel spills on the tunnel roadbed and catches fire. In the USA typically, the water density required for fixed firefighting systems is based on NFPA 13 and the minimum ventilation is based on smoke back layering. This work calculates the required water density based on the tunnel geometry and compares the back layering ventilation to the ventilation needed to remove saturated air. The presented methodology presents an analytical approach to calculate the water density and ventilation required to control a gasoline pool fire, which is a function of the size of the gasoline pool, without considering the growth restriction due to fuel depth and limited oxygen. The tunnel geometry parameters presented in the examples are limited to specific cross slopes and road slopes, as well as resultant fire sizes of 50 MW, 100 MW, and 150 MW. This work considers standard sprinkler heads to calculate the required density in conjunction with the ventilation required to maintain evaporative cooling. The calculations are performed with a water only system and with modifications that could be expected from the use of foam additive. Highlights: Fire size for liquid fuel fires can be calculated as a function of road geometry. The suppression rate may require an increase in the minimum ventilation rate. Foam systems contribute to reduction of the total fire size.